Eletrodos Quimicamente Modificados com Materiais Mistos Coloidais Argila/[CoOOH] Utilizados Como Sensores Eletroquímicos - Roloff, Lucéli (2012)
The chemically modified electrodes (CME) are electrodes with chemically active species, immobilized on their surfaces, in order to pre-establish and control physico-chemical nature of the interface electrode / solution. From the analytical point of view, sensitivity and /or selectivity of a determination must increase by the use of a CME, so its use is justified. CMEs clay has attracted the attention of many researchers because of their good electrochemical ion exchange capacity and lamellar structure. In this study it were used mixed materials (MMs) based on colloidal cobalt interaction [CoOOH] with clays aqueous suspensions like montmorillonite. These materials were used to modify the working electrode surface in order to generate an electrochemical sensor more sensitive and selective for redox species such as ascorbic acid (AA) and oxalic acid (OA). The MMs electrochemical behavior was studied using cyclic voltammetry (CV) and square wave voltammetry (SWV). Cyclic voltammograms of MMs showed anodic and cathodic peaks, attributed to the process Co (II) / Co (III), obtaining sharper peaks for higher scan rates. After SWV parameters optimization, it were calculated detection limits for the platinum electrode and for the electrode modified with the Colloidal Brasgel Cobalt material. In the presence of ascorbic acid, the value calculated for the platinum electrode was 6.65 x 10-7 mol. Lˉ¹ and for the electrode modified by the Co-Br material, was 3.28 x 10-5 mol Lˉ¹. In the presence of oxalic acid the platinum electrode does not act as acid sensor, thus there is no current change in the range of analyte concentration studied. The calculated detection limit for the Imported Sodium-Colloidal Cobalt material was 2.55 x 10-5 mol Lˉ¹.